Pengaruh Stigma Sosial terhadap Kepatuhan Pengobatan dan Luaran Klinis Pasien Kusta di Indonesia: A Systematic Literature Review - Monika Rai Islamiah (Lembaga Pengembangan Kinerja Dosen, 2026)
Leprosy remains a significant public health problem in Indonesia, affecting not only physical health but also creating substantial social consequences through stigma. Social stigma may influence patients’ health behaviors, including treatment adherence and therapeutic outcomes. This study aimed to examine the influence of social stigma on treatment adherence and clinical outcomes among leprosy patients in Indonesia using a Systematic Literature Review (SLR) approach. Literature searches were conducted across several scientific databases, focusing on studies published between 2022 and 2026. The selection process followed predetermined inclusion and exclusion criteria, resulting in 30 eligible articles for analysis. The review found that social stigma contributes to poor treatment adherence, delayed health-seeking behavior, reduced quality of life, and increased risk of mental health problems among people affected by leprosy. Family support, community support, health education, self-care interventions, and healthcare worker involvement were identified as important factors in reducing stigma and improving treatment success. The findings highlight the need to integrate social and psychological interventions with medical services to enhance treatment adherence and clinical outcomes among leprosy patients in Indonesia.